Сравнительный социологический анализ посткоммунистических трансформационных процессов (программа магистерского курса) - Бабенко, С. (Социология: теория, методы, маркетинг, 2007)
The course is developed for graduate students with major in sociology (MA level of education) who are acquainted with history of the sociological study of society and contemporary approaches in sociology. This course is focused on social changes in the contemporary world and transformation processes in post-communist countries in particular. A comparative focus of the course is built in two dimensions. The first one is to point out changes in our society comparatively to the Soviet stage of its development. The second one is to compare transformation processes in European post-Soviet countries with post-communist transformations in other European states. The course is intended to face students with the main problematics of a contemporary discussion and research on the social change theory, as well as with attempts to study the post-communist transformation processes in a comparative perspective.